Career Exploration Training to Improve Career Decision Making Self-Efficacy of High School Student in Bandung - Susanto, Kristofer Biaggi; Riasnugrahani , Missiliana; Savitri, Jane (Universitas Medan Area, 2024)
Currently, many high school students are confused and feel unsure when it comes to choosing their future major or career. The research conducted aims to see the impact of Career Exploration (CE) through a training program in improving Career Decision Making Self-Efficacy (CDMSE) of high school students in Bandung. This study uses an experimental method. There were 6 students in class XI who participated in the experimental group and the control group. Each participant completed a pre-test and post-test questionnaire for CE and CDMSE. The data analysis technique was carried out by different tests using the Mann-Whitney U and Wilcoxon Rank statistical tests with the help of the SPSS 25.0 program. It was found that CE, through the training program, can be significantly effective in improving the CDMSE of students. The results of the measurement of the magnitude of the effect stated that the intervention in the form of career exploration training had a great impact on CDMSE.